Температурное поле в кристалле иттрий-алюминиевого граната при двухстадийном выращивании - Kovtun, G. P.; Kravchenko, A. I.; Kondrik, A. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
Using computer simulation, the uniformity of the distribution of the temperature gradient modulus G(r) along the radius of a yttrium aluminum garnet crystal near the crystallization front was investigated at the transition from the accelerated to the slow growth stage, depending on the thermal conductivity of the conical part. Calculations were performed for different crystal and crucible diameters. It was found that there exists an optimal thermal conductivity value at which the most uniform distribution of G(r) at the crystallization front is achieved for small values of the gradient modulus G.